2013
DOI: 10.4172/jpb.s2-001
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Chemical Cross-linking Mass Spectrometry Perspectives

Abstract: The spectacular heterogeneity of a complex protein mixture from biological samples becomes even more difficult to tackle when one’s attention is shifted towards different protein complex topologies, transient interactions, or localization of PPIs. Meticulous protein-by-protein affinity pull-downs and yeast-two-hybrid screens are the two approaches currently used to decipher proteome-wide interaction networks. Another method is to employ chemical cross-linking, which gives not only identities of interactors, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 118 publications
(133 reference statements)
1
22
0
Order By: Relevance
“…This was effectively demonstrated by an in silico analysis that showed that substantially fewer zero-length cross-links were required to accurately reproduce a known protein structure via a modeling experiment, and to discard erroneous structures generated by modeling [23]. Moreover, because the reaction can only occur between residues that are roughly within salt bridge distance of each other, residue interactions captured by this method are more likely to describe direct contact sites rather than simply sites that are in close proximity [37]. In addition, zero-length cross-linking reagents are less likely to generate “dead-end” products, which occur when only one of the reactive groups is able to react with a site on a protein and the second site reacts either with water or a quenching reagent, compared to other cross-linkers.…”
Section: Zero-length Chemical Cross-linkingmentioning
confidence: 99%
See 1 more Smart Citation
“…This was effectively demonstrated by an in silico analysis that showed that substantially fewer zero-length cross-links were required to accurately reproduce a known protein structure via a modeling experiment, and to discard erroneous structures generated by modeling [23]. Moreover, because the reaction can only occur between residues that are roughly within salt bridge distance of each other, residue interactions captured by this method are more likely to describe direct contact sites rather than simply sites that are in close proximity [37]. In addition, zero-length cross-linking reagents are less likely to generate “dead-end” products, which occur when only one of the reactive groups is able to react with a site on a protein and the second site reacts either with water or a quenching reagent, compared to other cross-linkers.…”
Section: Zero-length Chemical Cross-linkingmentioning
confidence: 99%
“…This substantially complicates analysis of non-zero-length cross-link experiment data. Zero-length cross-link experiments are also less likely to generate “self-linked” products that occur when interacting reactive groups are on the same peptide [37], as both reactive groups would have to be on the same peptide and directly interact in a salt bridge. Dead-end and self-linked products of non-zero-length cross-linkers are problematic because they must be accounted for in database searches.…”
Section: Zero-length Chemical Cross-linkingmentioning
confidence: 99%
“…Relationships between two peptides from the same protein constituted the majority of identifications (intraprotein PPIs). Two residues within a single protein have a high likelihood of being in close physical contact within a cell, are therefore more frequently cross-linked, and make up a higher proportion of interactions in crosslinked datasets[22, 34]. Importantly, intraprotein interactions define proximal residues within a protein, and thereby provide valuable structural coordinates for identified proteins even when no known structure exists for this protein (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, chemical cross-links survive protein denaturation and digestion, and cross-linked peptide pairs, along with the cross-linking sites can be identified in a mass spectrometer. We recently reviewed this topic extensively in [36]. We also recommend earlier review by Trakselis et al, which discusses chemical cross-linking for structural analysis of protein complexes [37].…”
Section: Methods Of Protein-protein Interaction Discoverymentioning
confidence: 99%
“…As a consequence, in [36] we suggested that long-length cross-linkers, selective for frequently occurring amino acids, are useful for establishing identities of interacting partners; while shorter, broadly selective cross-linkers are better suited for analyzing structure of PPI interfaaces. An affinity handle, such as biotinyl, or alkynyl for conjugation using click-chemistry; and MS 2 -labile reporter groups can be introduced into a long-length cross-linker [39, 40].…”
Section: Methods Of Protein-protein Interaction Discoverymentioning
confidence: 99%